A case of acute tarsal tunnel syndrome following lateralizing calcaneal osteotomy. Issue 1 (March 2015) - Walls, Raymond J.; Chan, Jeremy Y.; Ellis, Scott J.
Highlights Tarsal tunnel syndrome is a rare complication of lateralizing calcaneal osteotomies in patients with CMT and cavovarus feet. We report the first case of iatrogenic tarsal tunnel syndrome in a patient without any pre-existing neurological disorder. Awareness of this complication and expedient surgical release can lead to a successful outcome.